Complexities of gene expression patterns in natural populations of an extremophile fish (Poecilia mexicana, Poeciliidae). Issue 16 (4th July 2017) - Passow, Courtney N.; Brown, Anthony P.; Arias‐Rodriguez, Lenin; Yee, Muh‐Ching; Sockell, Alexandra; Schartl, Manfred; Warren, Wesley C.; Bustamante, Carlos; Kelley, Joanna L.; Tobler, Michael
Abstract: Variation in gene expression can provide insights into organismal responses to environmental stress and physiological mechanisms mediating adaptation to habitats with contrasting environmental conditions. We performed an RNA‐sequencing experiment to quantify gene expression patterns in fish adapted to habitats with different combinations of environmental stressors, including the presence of toxic hydrogen sulphide (H2 S) and the absence of light in caves. We specifically asked how gene expression varies among populations living in different habitats, whether population differences were consistent among organs, and whether there is evidence for shared expression responses in populations exposed to the same stressors. We analysed organ‐specific transcriptome‐wide data from four ecotypes of Poecilia mexicana (nonsulphidic surface, sulphidic surface, nonsulphidic cave and sulphidic cave). The majority of variation in gene expression was correlated with organ type, and the presence of specific environmental stressors elicited unique expression differences among organs. Shared patterns of gene expression between populations exposed to the same environmental stressors increased with levels of organismal organization (from transcript to gene to physiological pathway). In addition, shared patterns of gene expression were more common between populations from sulphidic than populations from cave habitats, potentially indicating that physiochemical stressors with clear biochemical consequences can constrain the diversity of adaptive solutions that mitigate their adverse effects. Overall, our analyses provided insights into transcriptional variation in a unique system, in which adaptation to H2 S and darkness coincide. Functional annotations of differentially expressed genes provide a springboard for investigating physiological mechanisms putatively underlying adaptation to extreme environments.